Six Rites of Allied Harmony: Changes in Ancient Chinese Wedding Ceremonies under the Influence of Confucianism - Wu, Yu; Xu, Zhidiankui (2023)
Ancient Chinese wedding ceremonies served as the solemn rituals for witnessing and establishing marriage, primarily aimed at forging kinship ties between two families and fulfilling the obligations of ancestral worship and lineage continuation. Within the Confucian tradition, the family and the state have always been interconnected, and ancient Chinese weddings, dating back to the Zhou dynasty, have maintained the fundamental order of both the family and society. This article primarily explores the influence of Confucianism on ancient Chinese wedding rituals and customs, as well as the historical evolution of wedding ceremonies throughout different dynasties. According to Confucian principles, the main procedures of the wedding ceremony included six rituals: “Nacai” (proposal ceremony), “Wenming” (name inquiry), “Naji” (betrothal gift ceremony), “Nazheng” (gifts for the selection of the auspicious day), “Qingqi” (asking for a wedding date), and “Qinying” (wedding procession). These six rituals were collectively known as the “Six Rites”. This study found that, during the Qin and Han dynasties and the Tang and Song dynasties, there were two important stages of reform of wedding ceremonies under the influence of Confucianism. The “Six Rites” were streamlined and merged into the “Three Rites”, gradually becoming more secular. During the Ming and Qing dynasties, the interaction between Confucianism and the wedding ceremony weakened until the Republic of China period, when traditional constraints were broken. It is evident that the “Six Rites” have continued to serve as the template of traditional Chinese weddings and have been the important basis for subsequent wedding customs.
Keywords: wedding phenomena; Family Relations; ritual evolution; marriage customs culture; Confucianism; traditional Chinese weddings